Understanding military doctrine a multidisciplinary approach - Hoiback, Harald (Cass military studies, 2017)
This book puts military doctrine into a wider perspective, drawing on military history, philosophy, and political science. This book provides a theoretical understanding of such questions. Divided into three parts, the author investigates the historical roots of military doctrine and explores its growth and expansion until the present day, and goes on to analyse the main characteristics of a military doctrine. Using a multidisciplinary approach, the book concludes that doctrine can be utilized in three key ways: as a tool of command, as a tool of change, and as a tool of education.